Characterization of Frequently Mutated Cancer Genes and Tumor Mutation Burden in Chinese Breast Cancer - Xiao, Weikai; Zhang, Guochun; Chen, Bo; Chen, Xiaoqing; Wen, Lingzhu; Lai, Jianguo; Li, Xuerui; Li, Min; Liu, Hao; Liu, Jing; Han-Zhang, Han; Lizaso, Analyn; et al. (Frontiers in Oncology, 2021)
Objectives: Genomic changes, including ERBB2 amplification and mutation, PIK3CA, AKT1, ESR1 mutation and TMB, etc., have become targets of related therapies. This study aimed to further clarify mutational features related to the malignant features of breast cancer (BC). Methods: Tumors and matched whole blood were collected from 589 Chinese BC patients. The extracted DNA was used to analyze all types of genomic changes in 520 cancer-related genes, including: single nucleotide variation (SNV), insertion and deletion (Indel), copy number variation (CNV) and gene rearrangement. The NGS-based calculation algorithm also determines the tumor mutation burden (TMB) status. Results: A total of 18 genes (mutations: LPR1B, EGFR, POLE, PTPRT, KAT6A, HIST1H3C, LATS1, SDHA and SRC; amplification: MYC, BRIP1, NBN, CD79B, PREX2, RUNX1T1, PRKAR1A, PRKDC and NTK2) were more frequently mutated in T3-4 tumors as compared with T1-2 tumors (P<0.05). Twelve genes (mutation: POLE and TET2; amplification: ERBB2, CDK12, CCND1, RPS6KB2, AURKA, FGFR2, RPDM1, CDK4, CHD2 and FANCI) are more frequently mutated in tumors with lymph node metastasis, compared with those without lymph node metastasis (P <0.05). However，six genes (mutation: GATA3, FOXA1, ANKRD11 and RET; amplification: PIK3C2G and CCND2) were more frequently mutated in tumors without lymph node metastasis(P<0.05). Eleven genes (mutation: EZH2; amplification: PRKDC, RUNX1T1, IGF1R, IRS2, NTRK3, CARD11, FGFR3, LATS1, MEN1, PIK3CG, PPP6C and TRRAP) were more frequently mutated in young breast cancer. There were 11.4% (65/589) of patients had a total of 78 gene fusions: 12 ERBB2 (7 patients), 5 FGFR (4 FGFR2, 1 FGFR1), 4 ROS1, 4 MET, 4 CDK12, 3 ALK and 2 EGFR. 5.72% of GDPH BC patients have TMB greater than 10mut/Mb. In general, there is no difference between the TMB of Chinese breast cancer patients of various molecular subtypes and the corresponding subtype of TCGA breast cancer. However, the TMB of Chinese breast cancer and TCGA black breast cancer are statistically different in HR+/HER-, HR+/HER2+ and TNBC subtypes. Conclusions: This study revealed genomic changes and mutational features related to the malignant features of breast cancer. In addition, we provide new insights into the differences in breast cancer between East and West.